2021
DOI: 10.7759/cureus.18961
|View full text |Cite
|
Sign up to set email alerts
|

Photoallergy to Naproxen

Abstract: Reactions caused by photosensitivity, also called photodermatosis, are cutaneous reactions induced or exacerbated by exposure to electromagnetic radiation, including UV radiation, visible light, and infrared radiation. We present the case of a 41-year-old man with no personal history of allergy and who is referred to our Drug Allergy Unit for study. We performed a conventional patch test (non-irradiated) and photopatch (with the application of UVA) with reading at 48 and 96 hours and 24 hours after irradiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…There is extensive literature that explores the chemical and biological basis of druginduced photosensitivity [72,[74][75][76][77][78] but not much in the case of cosmetics. In this context, a recent examination by Hofmann et al [69] identified a total of 393 distinct drugs or drug compounds reported as photosensitizers.…”
Section: Discussionmentioning
confidence: 99%
“…There is extensive literature that explores the chemical and biological basis of druginduced photosensitivity [72,[74][75][76][77][78] but not much in the case of cosmetics. In this context, a recent examination by Hofmann et al [69] identified a total of 393 distinct drugs or drug compounds reported as photosensitizers.…”
Section: Discussionmentioning
confidence: 99%